Effects of pine sawdust and shrimp shell biochar on anaerobic digestion under different acidification conditions. Issue 1 (February 2022) - Wenjing, Tian; Qin, Jiang; Liu, Junyan; Liu, Feng; Gu, Li
Abstract: Effects of different types of biochar (pine sawdust biochar (PSBC) and shrimp shell biochar (SSBC) on anaerobic digestion under different acidification conditions were studied and compared. Compared with PSBC, SSBC had more alkaline functional groups and higher conductivity. As a result, PSBC and SSBC posed different impacts on the anaerobic digestion system under different acid inhibition conditions. In the case of less acidification, PSBC and SSBC reduced the lag time in methane production from 10.2 d to 6.3 d and 3.5 d, but didn't present significantly improvement in the final CH4 production. But regarding more serious acid stress, PSBC-added and SSBC-added digesters respectively obtained the specific methane yield of 266.8 and 280.0 mL CH4 /g VSS, 7.6% and 12.9% higher than the control digester. Both PSBC and SSBC showed pH buffering potency and the ability to promote the degradation of volatile fatty acids, while the latter was superior to the former. On the one hand, this might be due to more basic functional groups and more areas for microbial attachment existing on the surface of SSBC, which was expected to buffer the acid shock and promote microbial growth; on the other hand, according to microbial diversity analysis, the SSBC was likely to stimulate direct interspecific electron transfer, thereby accelerating methane production. Graphical Abstract: ga1 Highlights: Shrimp shell biochar (13%) got higher CH4 promotion than pine sawdust biochar (8%). Biochar's superiority is more pronounced in more severe acidification conditions. Biochar with higher conductivity stimulated direct interspecific electron transfer.